Anthropogenic Air Pollution Delays Marine Stratocumulus Breakup to Open Cells. Issue 23 (6th December 2019) - Goren, Tom; Kazil, Jan; Hoffmann, Fabian; Yamaguchi, Takanobu; Feingold, Graham
Abstract: Marine stratocumulus cloud (Sc) decks with high cloud fraction typically breakup when sufficient drizzle forms. Cloud breakup leads to a lower cloud radiative effect due to the lower cloud amount. Here we use realistic Lagrangian large eddy simulations along a 3‐day trajectory, evaluated with satellite observations, to investigate the timing of Sc breakup in response to aerosol conditions. We show that the timing of the breakup is strongly modulated by the diurnal cycle and large‐scale meteorology but varies systematically with the initial aerosol concentration: the more polluted the clouds, the later the breakup. This indicates that the cloud radiative effect via cloud cover adjustments is not saturated, in contrast to the effect of aerosol on cloud albedo at fixed cloudiness, which weakens with increasing aerosol levels. The results also show that the cloud radiative impact of anthropogenic aerosol is strongest far from its origin over land. Key Points: Marine stratocumulus cloud breakup time is systematically delayed with increasing initial background aerosol concentration Cloud cover response to aerosol is not saturated, in contrast to the effect of aerosol on cloud albedo at fixed cloudiness Realistic Lagrangian large eddy simulations identify the roles of both aerosol and meteorology in determining cloud breakup time